AOX kit / Muhammad Noor Imraan Mohamed Yahya - Mohamed Yahya, Muhammad Noor Imraan (2020)
Antioxidants are very crucial in daily diet to fight against the free radicals. Free radicals always develop in our body systems and this cause damages to our body cells. Huge amount of antioxidants is required to eliminate those free radicals, thus preventing cancer developments and heart diseases among aging people. In this new era of technology, Aox Kit is the only method to determine the amount of antioxidants for our foods in an innovative, creative and simple way that did not cost a lot of money. In many industries, they determine an antioxidant with ORAC-ESSAY that too expensive and take a lot of time. Vigilance on the amount of antioxidants in our daily meal is ensures that our body is well prepared to fight against the free radicals that constantly produced in our body. Aox Kit introduces an innovative way in measuring concentration of antioxidants by only using a mobile application, called "Colour Name". Hence, our main objective to address awareness of antioxidants and reduce the risk of getting cancer can be achieved.